Role of Hel308 helicase in origin-independent DNA replication in two species of Haloferax - Harrison, Catherine (2024)
DNA replication is a process which is essential to all forms of life. This process is initiated at defined points, known as origins of replication. Origins are universal, and were previously believed to be essential. However, the halophilic euryarchaeon Haloferax volcanii is able to survive in the absence of origins, and in fact, origin-deleted mutants grow faster than the wild-type. Growth in these circumstances is thought to be dependent on recombination-dependent replication, since the recombinase protein RadA is essential in origin-deleted cells.